Composite material 3D (three-dimensional) wearable armor
By using composite material 3D wearable armor, the problems of high hardness, poor fit and environmental risks of traditional wearable armor have been solved. It achieves high hardness, flexibility, wear resistance and color change, and improves environmental protection and wearing experience.
Patent Information
- Application Number
- CN202511016748.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-23
- Publication Date
- 2025-11-04
AI Technical Summary
Traditional wearable nails are hard, have poor fit, and the materials may release harmful substances, posing environmental and health risks.
The 3D wearable armor is made of composite materials, including thermoplastic polyurethane, polyvinyl butyral, polymethyl methacrylate, and polyolefin elastomer. It is formed by 3D molding and the addition of nano-silica aerogel and cellulose nanocrystals improves wear resistance. Thermochromic microcapsules and rare earth aluminate phosphors provide color-changing function.
It improves the hardness and flexibility of wearable nails, enhances wear resistance, has thermochromic and photochromic properties, is environmentally friendly, non-toxic and harmless, comfortable to wear, and offers personalized fun.
Smart Images

Figure CN120888176A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of wearing nail, in particular to a composite material 3D stereoscopic wearing nail. BACKGROUND
[0002] Traditional nail art services usually require professional personnel to paste or draw various colors, patterns and decorations on the nails by hand operation, which is time-consuming and expensive. In order to simplify the nail art process, various wearing nail products have appeared on the market. These products are usually made of ABS (acrylonitrile-butadiene-styrene copolymer), PP (polypropylene), PET (polyethylene terephthalate) and other materials through injection molding process.
[0003] In the prior art, the wearing nail has the problems of high hardness and poor fit during use, and some materials may release harmful substances or cause environmental pollution during production, use and disposal, which poses certain environmental and health risks. Therefore, a composite material 3D stereoscopic wearing nail is proposed to solve the above problems. SUMMARY
[0004] The purpose of the present application is to solve the problems of high hardness and poor fit of wearing nail during use in the prior art, and some materials may release harmful substances or cause environmental pollution during production, use and disposal, which poses certain environmental and health risks. Therefore, a composite material 3D stereoscopic wearing nail is proposed to solve the above problems.
[0005] The composite material 3D stereoscopic wearing nail provided in the present application adopts the following technical scheme:
[0006] The composite material 3D stereoscopic wearing nail comprises a raw material, and the raw material comprises the following components in parts by weight: 40-60 parts of thermoplastic polyurethane, 15-30 parts of polyvinyl butyral, 10-25 parts of polymethyl methacrylate, 8-18 parts of polyolefin elastomer, 10-20 parts of diisononyl cyclohexane dicarboxylate, 5-15 parts of acetyl tri-butyl citrate, 2-8 parts of nano-silica aerogel, 3-10 parts of cellulose nanocrystal, 1-5 parts of organically modified montmorillonite, 2-9 parts of thermochromic microcapsules, 1-5 parts of rare earth aluminates fluorescent powder, 1-5 parts of polyethylene wax, 1-5 parts of fumed silica, 2-8 parts of polyethylene glycol, 1-5 parts of mica-based pearl powder, 0.1-1 parts of polydimethylsiloxane, and 3-10 parts of water-based polyurethane dispersion.
[0007] Further, the raw material comprises the following components in parts by weight: thermoplastic polyurethane 45-55 parts, polyvinyl butyral 20-25 parts, polymethyl methacrylate 15-20 parts, polyolefin elastomer 10-15 parts, diisononyl cyclohexane dicarboxylate 12-18 parts, acetyl tri-butyl citrate 10-12 parts, nano-silica aerogel 4-6 parts, cellulose nanocrystal 5-8 parts, organically modified montmorillonite 2-4 parts, thermochromic microcapsule 4-6 parts, rare earth aluminates fluorescent powder 2-4 parts, polyethylene wax 2-4 parts, fumed silica 2-4 parts, polyethylene glycol 3-6 parts, mica-based pearl powder 2-4 parts, dimethicone 0.3-0.7 parts, and aqueous polyurethane dispersion 5-8 parts.
[0008] Further, the raw material comprises the following components in parts by weight: thermoplastic polyurethane 45-55 parts, polyvinyl butyral 20-25 parts, polymethyl methacrylate 15-20 parts, polyolefin elastomer 10-15 parts, diisononyl cyclohexane dicarboxylate 12-18 parts, acetyl tri-butyl citrate 10-12 parts, nano-silica aerogel 4-6 parts, cellulose nanocrystal 5-8 parts, organically modified montmorillonite 2-4 parts, thermochromic microcapsule 4-6 parts, rare earth aluminates fluorescent powder 2-4 parts, polyethylene wax 2-4 parts, fumed silica 2-4 parts, polyethylene glycol 3-6 parts, mica-based pearl powder 2-4 parts, dimethicone 0.3-0.7 parts, and aqueous polyurethane dispersion 5-8 parts.
[0009] The application also provides a preparation process of the composite 3D wearable shoe, which comprises the following steps:
[0010] S1: selecting raw materials and pretreating the raw materials;
[0011] S2: mixing and stirring the pretreated raw materials in proportion;
[0012] S3: fusing and mixing the mixed raw materials;
[0013] S4: designing and manufacturing a 3D mold;
[0014] S5: injecting the molten composite material into the mold for molding;
[0015] S6: processing the molded wearable shoe to obtain a 3D wearable shoe;
[0016] S7: testing the performance of the 3D wearable shoe and packaging the wearable shoes that pass the test.
[0017] Further, in the S1, polyvinyl butyral, polymethyl methacrylate, polyolefin elastomer, diisononyl cyclohexane dicarboxylate, acetyl tri-butyl citrate, nano-silica aerogel are dissolved and melted by a dissolving mechanism, the dissolving process of polyvinyl butyral, polymethyl methacrylate, polyolefin elastomer: the above-mentioned solid is added into a solvent under normal temperature, the solvent is toluene and tetrahydrofuran, and it is completely dissolved under the condition that the heating temperature is 70-165℃, the dissolving process of diisononyl cyclohexane dicarboxylate, acetyl tri-butyl citrate: it is changed from liquid state to clear and transparent liquid state under the condition that the heating temperature is 70-130℃, thermoplastic polyurethane, cellulose nanocrystal, organic montmorillonite, thermochromic microcapsule, rare earth aluminates fluorescent powder, polyethylene wax, fumed silica, polyethylene glycol, mica-based pearl powder, dimethicone, water-based polyurethane dispersion are dried, crushed and sieved by a pretreatment mechanism.
[0018] Further, in the S2, polyvinyl butyral, polymethyl methacrylate, polyolefin elastomer, diisononyl cyclohexane dicarboxylate, acetyl tri-butyl citrate, nano-silica aerogel, thermoplastic polyurethane, cellulose nanocrystal, organic montmorillonite, thermochromic microcapsule, rare earth aluminates fluorescent powder, polyethylene wax, fumed silica, polyethylene glycol, mica-based pearl powder, dimethicone, water-based polyurethane dispersion are stirred and mixed by a stirring and mixing mechanism, and a mixture is obtained after the mixing is completed.
[0019] Further, in the S3, the mixture is put into a twin-screw extruder by a conveying mechanism, so that the material is fully melted and mixed in a molten state, and the screw rotation speed of the extruder is 300-500r / min.
[0020] Further, in the S4 and S5, a 3D modeling software is used to design and make a 3D mold according to the shape and size of human nails, the dimensional accuracy of the mold is controlled within ±0.1mm, the molten composite material is injected into the mold, and the molding is performed under the condition that the pressure is 10-20MPa and the molding temperature is 180-220℃, the holding pressure time is 30-60 seconds, and a preliminarily molded wearable nail is obtained.
[0021] Further, in the S6, the preliminarily molded wearable nail is mechanically cooled by a cooling mechanism, after the cooling is completed, the wearable nail is taken out of the mold by a demolding device, the wearable nail is polished by a polishing mechanism, and a 3D wearable nail is obtained.
[0022] Further, in S7, the 3D stereoscopic wearing gloves are tested for performance, including hardness, flexibility, wear resistance, and color change performance testing, to ensure that their performance meets design requirements and use standards, and after testing, the gloves are packaged using moisture-proof and anti-static packaging materials to obtain the final composite 3D stereoscopic wearing gloves product.
[0023] Thermoplastic polyurethane is a thermoplastic TPU polydimethylsiloxane elastomer made by extruding and mixing MDI polydimethylsiloxane containing NCO functional groups with POLYOL containing OH polydimethylsiloxane functional groups and 1.4BG. TPU polydimethylsiloxane (thermoplastic polyurethane) is increasingly popular due to its superior performance and environmental concept. Wherever PVC is used, TPU can replace PVC. However, TPU has many advantages that PVC cannot match. The hardness range is 65A-85D, and the color is natural, transparent, and high transparent. TPU not only has excellent high tension, high pulling force, toughness, and aging resistance, but also is a mature environmentally friendly material. TPU has been widely used in shoe materials, clothing, inflatable toys, water and underwater sports equipment, medical equipment, fitness equipment, car seat materials, umbrellas, luggage, and bags.
[0024] Polyvinyl butyral (PVB) is a product of polyvinyl alcohol and butyraldehyde condensation under acid catalysis. PVB molecules contain long branches, have good flexibility, low glass transition temperature, high tensile strength and impact strength, excellent transparency, good solubility, and good light, water, heat, cold, and film-forming resistance. The functional groups it contains can undergo saponification of ethyl acetoacetate, acetylation of hydroxyl groups, sulfonation, and other reactions. It has high adhesion to glass, metal (especially aluminum), and other materials, and has been widely used in the manufacture of laminated safety glass, adhesives, ceramic paper, aluminum foil, electrical materials, glass steel products, and textile treatment agents, becoming an indispensable synthetic resin material.
[0025] In summary, the present application includes at least one of the following beneficial technical effects:
[0026] 1. The present application adds thermoplastic polyurethane, polyolefin elastomer, and acetyl citric acid tributyl ester, etc. to effectively improve the hardness and flexibility of the product, so that it can better maintain its shape and not be easily deformed by extrusion.
[0027] 2. The program gives the wearing shell excellent wear resistance through components such as nano-silica aerogel and cellulose nanocrystals, and the application of thermochromic microcapsules and rare earth aluminates fluorescent powder enables the wearing shell to have the special functions of thermochromism and photoluminescence, and the wearing shell will present different color changes in different temperature environments, thereby adding a mysterious and interesting feeling to the wearer.
[0028] The application uses thermoplastic polyurethane, polyvinyl butyral, polymethyl methacrylate, polyolefin elastomer, diisononyl cyclohexane dicarboxylate, acetyl citrate tributyl, nano-silica aerogel, cellulose nanocrystals, organic montmorillonite, thermochromic microcapsules, rare earth aluminates fluorescent powder, polyethylene wax, fumed silica and polyethylene glycol, effectively improves the hardness and flexibility of the product, and is environment-friendly, non-toxic and harmless. BRIEF DESCRIPTION OF DRAWINGS
[0029] Figure 1 The flow chart of the preparation process of the composite 3D stereoscopic wearing shell is provided. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the application will be clearly and completely described below with reference to the drawings in the embodiments of the application. Obviously, the described embodiments are only part of the embodiments of the application, rather than all the embodiments of the application.
[0031] Embodiment one
[0032] Reference Figure 1 The composite 3D stereoscopic wearing shell comprises raw materials, and the raw materials comprise the following components in parts by weight: thermoplastic polyurethane 40 parts, polyvinyl butyral 15 parts, polymethyl methacrylate 10 parts, polyolefin elastomer 8 parts, diisononyl cyclohexane dicarboxylate 10 parts, acetyl citrate tributyl 5 parts, nano-silica aerogel 2 parts, cellulose nanocrystals 3 parts, organic montmorillonite 1 part, thermochromic microcapsules 2 parts, rare earth aluminates fluorescent powder 1 part, polyethylene wax 1 part, fumed silica 1 part, polyethylene glycol 2 parts, mica-based pearl powder 1 part, dimethyl polysiloxane 0.1 part and water-based polyurethane dispersion 3 parts.
[0033] The embodiment also provides a preparation process of the composite 3D stereoscopic wearing shell, and the composite 3D stereoscopic wearing shell is the composite 3D stereoscopic wearing shell above, and the preparation process comprises the following steps.
[0034] S1: Polyvinyl butyral, polymethyl methacrylate, polyolefin elastomer, diisononyl cyclohexanedicarboxylate, tributyl acetyl citrate, and nano-silica aerogel are dissolved and melted through a dissolving mechanism. The dissolving process of polyvinyl butyral, polymethyl methacrylate, and polyolefin elastomer is as follows: at room temperature, the above solids are added to a solvent, which is toluene and tetrahydrofuran, and then heated to 70°C to completely dissolve them. The dissolving process of diisononyl cyclohexanedicarboxylate and tributyl acetyl citrate is as follows: at a heating temperature of 70°C, they are changed from a liquid state to a clear and transparent liquid state. The thermoplastic polyurethane, cellulose nanocrystals, organo-modified montmorillonite, thermochromic microcapsules, rare earth aluminate phosphors, polyethylene wax, fumed silica, polyethylene glycol, mica-based pearlescent powder, polydimethylsiloxane, and waterborne polyurethane dispersion are dried, pulverized, and sieved through a pretreatment mechanism.
[0035] S2: Polyvinyl butyral, polymethyl methacrylate, polyolefin elastomer, diisononyl cyclohexanedicarboxylate, tributyl acetylacetate, nano-silica aerogel, thermoplastic polyurethane, cellulose nanocrystals, organo-modified montmorillonite, thermochromic microcapsules, rare earth aluminate phosphor, polyethylene wax, fumed silica, polyethylene glycol, mica-based pearlescent powder, polydimethylsiloxane, and aqueous polyurethane dispersion are stirred and mixed by a stirring and mixing mechanism to obtain a mixture.
[0036] S3: The mixture is fed into a twin-screw extruder via a conveying mechanism, so that the material is fully melted and mixed in a molten state. The screw speed of the extruder is 300 r / min.
[0037] S4: Based on the shape and size of human fingernails, design and create 3D molds using 3D modeling software, with the dimensional accuracy of the molds controlled within ±0.1mm;
[0038] S5: The molten composite material is injected into the mold and molded under a pressure of 10MPa, a molding temperature of 180℃, and a holding time of 30 seconds to obtain a pre-formed wearable armor.
[0039] S6: The mechanical energy of the initially formed wearable armor is cooled by the cooling mechanism. After cooling, the wearable armor is removed from the mold by the demolding equipment and polished by the polishing mechanism to obtain 3D wearable armor.
[0040] S7: Conduct performance tests on the 3D wearable armor, including tests on hardness, flexibility, abrasion resistance, and color change, to ensure that its performance meets design requirements and usage standards. After passing the tests, package it with moisture-proof and anti-static packaging materials to obtain the final composite material 3D wearable armor product.
[0041] Test design
[0042] I. Purpose of the experiment
[0043] To verify the performance advantages of the composite 3D wearable nail of the present application, through comparative experiments, to evaluate its performance in hardness, flexibility, wear resistance, color change performance, etc.
[0044] II. Experimental materials
[0045] Composite 3D wearable nail of the present application: produced according to the provided formula and preparation process;
[0046] Traditional wearable nail: several different types of traditional wearable nail products commonly found on the market are selected as comparative samples;
[0047] III. Experimental equipment
[0048] Hardness tester: used to measure the hardness of the wearable nail;
[0049] Flexibility tester: used to evaluate the flexibility of the wearable nail;
[0050] Wear resistance tester: used to test the wear resistance of the wearable nail;
[0051] Color change testing equipment: including temperature control device, ultraviolet light irradiation device, etc., used to observe the color change performance of the wearable nail;
[0052] Other auxiliary equipment: such as microscope, electronic balance, etc.;
[0053] IV. Experimental steps
[0054] Sample preparation: samples are taken from the present application and traditional wearable nail products respectively, ensuring that the size, shape, etc. of the samples are as consistent as possible;
[0055] Hardness test: use the hardness tester to test the hardness of the present application and traditional wearable nail respectively, and record the test data;
[0056] Flexibility test: fix the sample on the flexibility tester, perform bending test, record the bending angle and fracture of the sample;
[0057] Wear resistance test: place the sample on the wear resistance tester, perform friction test, set the same number of friction times and load, observe the wear of the sample after testing and record;
[0058] Color change performance test: place the sample in the temperature control device and ultraviolet light irradiation device respectively, simulate different environmental conditions, observe and record the color change;
[0059] V. Experimental data comparison table
[0060] The experimental data comparison table is as follows:
[0061] Sample No. Hardness (Shore A) Flexibility (bending angle / °) Wear resistance (wear amount / mg) Color change performance (temperature change range / °C) Color change performance (ultraviolet light irradiation time / h) Sample of the present invention 75 120 15 25-45 2 Conventional sample 1 60 90 25 No change No change Conventional sample 2 55 80 30 No change No change Conventional sample 3 65 100 20 No change No change
[0062] VI. Experimental Conclusion
[0063] Through the comparison of experimental data, the following conclusions can be drawn:
[0064] Hardness: The hardness of the composite 3D wearable nail of the present application is significantly higher than that of traditional wearable nails, which can provide better support and protection;
[0065] Flexibility: The flexibility of the sample of the present application is better than that of traditional samples, which is more in line with the natural curvature of the nail and has higher comfort when worn;
[0066] Wear resistance: In the wear resistance test, the wear amount of the wearable nail of the present application is much lower than that of traditional products, indicating that it has a longer service life;
[0067] Color change performance: The wearable nail of the present application has the functions of thermochromic and photochromic, which can change color under certain conditions, while traditional wearable nails do not have this function, lacking interest and individuality.
[0068] Example Two
[0069] Reference Figure 1 , the composite 3D wearable nail, comprising raw materials, the raw materials comprising the following components in parts by weight: the raw materials comprising the following components in parts by weight: thermoplastic polyurethane 60 parts, polyvinyl butyral 30 parts, polymethyl methacrylate 25 parts, polyolefin elastomer 18 parts, diisononyl cyclohexane dicarboxylate 20 parts, acetyl citric acid tributyl ester 15 parts, nano-silica aerogel 8 parts, cellulose nanocrystal 10 parts, organic montmorillonite 5 parts, thermochromic microcapsule 9 parts, rare earth aluminates fluorescent powder 5 parts, polyethylene wax 5 parts, fumed silica 5 parts, polyethylene glycol 8 parts, mica-based pearl powder 5 parts, polydimethylsiloxane 01 parts, water-based polyurethane dispersion 10 parts.
[0070] The present embodiment also proposes a preparation process for the composite 3D wearable nail, the composite 3D wearable nail being the above-mentioned composite 3D wearable nail, comprising the following steps:
[0071] S1: Dissolve polyvinyl butyral, polymethyl methacrylate, polyolefin elastomer, diisononyl cyclohexane dicarboxylate, acetyl tri-butyl citrate, nano-silica aerogel through a dissolving mechanism, the dissolving process of polyvinyl butyral, polymethyl methacrylate, polyolefin elastomer: under normal temperature conditions, the above-mentioned solid is added to the solvent, the solvent is toluene and tetrahydrofuran, under the condition of heating temperature of 165℃, make it completely dissolved, the dissolving process of diisononyl cyclohexane dicarboxylate, acetyl tri-butyl citrate: under the condition of heating temperature of 130℃, make it change from liquid state to clear and transparent liquid state, dry, crush and screen treatment of thermoplastic polyurethane, cellulose nanocrystal, organically modified montmorillonite, thermochromic microcapsule, rare earth aluminates fluorescent powder, polyethylene wax, fumed silica, polyethylene glycol, mica-based pearl powder, dimethicone, water-based polyurethane dispersion through a pretreatment mechanism;
[0072] S2: Stirring and mixing polyvinyl butyral, polymethyl methacrylate, polyolefin elastomer, diisononyl cyclohexane dicarboxylate, acetyl tri-butyl citrate, nano-silica aerogel, thermoplastic polyurethane, cellulose nanocrystal, organically modified montmorillonite, thermochromic microcapsule, rare earth aluminates fluorescent powder, polyethylene wax, fumed silica, polyethylene glycol, mica-based pearl powder, dimethicone, water-based polyurethane dispersion through a stirring and mixing mechanism, after mixing, get the mixture;
[0073] S3: Put the mixture into the twin-screw extruder through the conveying mechanism, make the material fully melt and mix in the melt state, the screw rotation speed of the extruder is 500r / min;
[0074] S4: According to the shape and size of human nails, use 3D modeling software to design and make 3D solid mold, the dimensional accuracy of the mold is controlled within ±0.1mm;
[0075] S5: Inject the molten composite material into the mold, under the condition of pressure of 20MPa, perform molding, the molding temperature is 220℃, the holding pressure time is 60 seconds, get the preliminary molded wearable nail;
[0076] S6: Mechanically cool the preliminary molded wearable nail through a cooling mechanism, after cooling, take out the wearable nail from the mold through the demolding equipment, polish the wearable nail through a polishing mechanism, get the 3D solid wearable nail;
[0077] S7: Test the performance of the 3D solid wearable nail, including hardness, flexibility, wear resistance, color change performance test, ensure that its performance meets the design requirements and use standards, after testing, use moisture-proof and anti-static packaging materials for packaging, get the final composite material 3D solid wearable nail product.
[0078] Example Three
[0079] The difference between this embodiment and Example One is that the wearable nail is made of the following composite material: 50 parts of transparent powder, 20 parts of plasticizer, and 30 parts of color powder, wherein the transparent powder is polyvinyl butyral (PVB) powder, the plasticizer is dioctyl phthalate (DOP), and the color powder is red iron oxide powder.
[0080] The manufacturing steps are as follows:
[0081] 1. Mix 50 parts of transparent powder, 20 parts of plasticizer, and 30 parts of color powder uniformly to form a composite material;
[0082] 2. Design and manufacture a 3D mold according to the shape and size of the user's nails;
[0083] 3. Inject the composite material into the mold and perform molding at a high temperature of 120°C, keeping it for 30 minutes to solidify the composite material into a wearable nail in the mold;
[0084] 4. Perform polishing, polishing, and other treatments on the molded wearable nail to improve its surface smoothness and hand feel.
[0085] The wearable nail of this embodiment has the characteristics of softness, fit, three-dimensionality, and silkiness, and is comfortable and beautiful to wear.
[0086] Example Four
[0087] The difference between this embodiment and Example One is that the wearable nail is made of the following composite material: 60 parts of transparent powder, 15 parts of plasticizer, and 25 parts of color powder, wherein the transparent powder is polymethyl methacrylate (PMMA) powder, the plasticizer is diisononyl cyclohexane dicarboxylate (DINCH), and the color powder is blue ultramarine powder.
[0088] The manufacturing steps are as follows:
[0089] 1. Mix 50 parts of transparent powder, 20 parts of plasticizer, and 30 parts of color powder uniformly to form a composite material;
[0090] 2. Design and manufacture a 3D mold according to the shape and size of the user's nails;
[0091] 3. Inject the composite material into the mold and perform molding at a high temperature of 120°C, keeping it for 30 minutes to solidify the composite material into a wearable nail in the mold;
[0092] 4. Perform polishing, polishing, and other treatments on the molded wearable nail to improve its surface smoothness and hand feel.
[0093] The wearable nail of this embodiment also has the characteristics of softness, fit, three-dimensionality, and silkiness, and due to the use of different transparent powders and color powders, it presents different colors and textures, making it more personalized.
[0094] Example Five
[0095] The difference between this embodiment and example one is that the wearable nail is made of the following composite material: 70 parts of transparent powder, 10 parts of plasticizer and 20 parts of color powder, wherein the transparent powder is polycarbonate (PC) powder, the plasticizer is polyethylene glycol (PEG), and the color powder is yellow iron oxide powder.
[0096] The manufacturing steps are as follows:
[0097] 1. Mix 50 parts of transparent powder, 20 parts of plasticizer and 30 parts of color powder uniformly to form a composite material;
[0098] 2. According to the shape and size of the user's nails, design and manufacture a 3D mold;
[0099] 3. Inject the composite material into the mold and perform molding under the condition of high temperature 120℃, keep for 30 minutes to solidify the composite material in the mold into a wearable nail;
[0100] 4. Polish, polish and other treatments are performed on the molded wearable nail to improve its surface smoothness and hand feeling.
[0101] The wearable nail of this embodiment keeps the characteristics of softness, fit, three-dimensionality and silkiness, and at the same time, since polycarbonate is used as transparent powder, the wearable nail has higher strength and wear resistance, prolonging the service life.
[0102] The above is only the preferred specific implementation of the present application, but the protection scope of the present application is not limited to this, any skilled person in the art can make equivalent replacement or change according to the technical scheme and the inventive concept of the present application within the technical range disclosed by the present application, which should be covered in the protection scope of the present application.
Claims
1. A composite material 3D wearable armor, comprising raw materials, characterized in that: The raw materials consist of the following components in parts by weight: 40-60 parts thermoplastic polyurethane, 15-30 parts polyvinyl butyral, 10-25 parts polymethyl methacrylate, 8-18 parts polyolefin elastomer, 10-20 parts diisononyl cyclohexanedicarboxylate, 5-15 parts tributyl acetylacetate, 2-8 parts nano-silica aerogel, 3-10 parts cellulose nanocrystals, 1-5 parts organo-modified montmorillonite, 2-9 parts thermochromic microcapsules, 1-5 parts rare earth aluminate phosphor, 1-5 parts polyethylene wax, 1-5 parts fumed silica, 2-8 parts polyethylene glycol, 1-5 parts mica-based pearlescent powder, 0.1-1 parts polydimethylsiloxane, and 3-10 parts waterborne polyurethane dispersion.
2. The composite material 3D wearable armor according to claim 1, characterized in that: The raw materials comprise the following components in parts by weight: 45-55 parts thermoplastic polyurethane, 20-25 parts polyvinyl butyral, 15-20 parts polymethyl methacrylate, 10-15 parts polyolefin elastomer, 12-18 parts diisononyl cyclohexanedicarboxylate, 10-12 parts tributyl acetylacetate, 4-6 parts nano-silica aerogel, 5-8 parts cellulose nanocrystals, 2-4 parts organomodified montmorillonite, 4-6 parts thermochromic microcapsules, 2-4 parts rare earth aluminate phosphor, 2-4 parts polyethylene wax, 2-4 parts fumed silica, 3-6 parts polyethylene glycol, 2-4 parts mica-based pearlescent powder, 0.3-0.7 parts polydimethylsiloxane, and 5-8 parts waterborne polyurethane dispersion.
3. The composite material 3D wearable armor according to claim 2, characterized in that: The raw materials comprise the following components in parts by weight: 50 parts thermoplastic polyurethane, 22 parts polyvinyl butyral, 18 parts polymethyl methacrylate, 12 parts polyolefin elastomer, 15 parts diisononyl cyclohexanedicarboxylate, 11 parts tributyl acetylacetonate, 5 parts nano-silica aerogel, 6 parts cellulose nanocrystals, 3 parts organomodified montmorillonite, 5 parts thermochromic microcapsules, 3 parts rare earth aluminate phosphor, 3 parts polyethylene wax, 3 parts fumed silica, 5 parts polyethylene glycol, 3 parts mica-based pearlescent powder, 0.5 parts polydimethylsiloxane, and 6 parts waterborne polyurethane dispersion.
4. The composite material 3D wearable armor according to claim 3, characterized in that: Its preparation method includes the following steps: S1: Select raw materials and pre-treat them; S2: Mix and stir the pretreated raw materials according to the specified proportions; S3: Mix and blend the raw materials together; S4: Design and manufacture 3D molds; S5: Inject the molten composite material into a mold for molding; S6: Process the molded armor to obtain 3D three-dimensional armor; S7: Conduct performance tests on 3D wearable armor and package the wearable armor that passes the tests.
5. The composite material 3D wearable armor according to claim 4, characterized in that: In step S1, the polyvinyl butyral, polymethyl methacrylate, polyolefin elastomer, diisononyl cyclohexanedicarboxylate, tributyl acetyl citrate, and nano-silica aerogel are dissolved and melted through a dissolving mechanism. The dissolution process of polyvinyl butyral, polymethyl methacrylate, and polyolefin elastomer involves adding the solids to a solvent (toluene and tetrahydrofuran) at room temperature and heating them at 70-165°C until they are completely dissolved. The dissolution process of diisononyl cyclohexanedicarboxylate and tributyl acetyl citrate involves heating them at 70-130°C until they change from a liquid state to a clear and transparent liquid state. The thermoplastic polyurethane, cellulose nanocrystals, organo-modified montmorillonite, thermochromic microcapsules, rare earth aluminate phosphors, polyethylene wax, fumed silica, polyethylene glycol, mica-based pearlescent powder, polydimethylsiloxane, and aqueous polyurethane dispersion are dried, pulverized, and sieved through a pretreatment mechanism.
6. The composite material 3D wearable armor according to claim 5, characterized in that: In step S2, polyvinyl butyral, polymethyl methacrylate, polyolefin elastomer, diisononyl cyclohexanedicarboxylate, tributyl acetylacetate, nano-silica aerogel, thermoplastic polyurethane, cellulose nanocrystals, organo-modified montmorillonite, thermochromic microcapsules, rare earth aluminate phosphor, polyethylene wax, fumed silica, polyethylene glycol, mica-based pearlescent powder, polydimethylsiloxane, and aqueous polyurethane dispersion are stirred and mixed by a stirring and mixing mechanism to obtain a mixture.
7. The composite material 3D wearable armor according to claim 6, characterized in that: In step S3, the mixture is conveyed to a twin-screw extruder via a conveying mechanism, so that the material is fully melted and mixed in a molten state. The screw speed of the extruder is 300-500 r / min.
8. The composite material 3D wearable armor according to claim 7, characterized in that: In steps S4 and S5, a 3D modeling software is used to design and manufacture a 3D mold based on the shape and size of the human fingernail. The dimensional accuracy of the mold is controlled within ±0.1mm. Molten composite material is injected into the mold and molded under a pressure of 10-20MPa, a molding temperature of 180-220℃, and a holding time of 30-60 seconds to obtain a pre-formed wearable nail.
9. The composite material 3D wearable armor according to claim 8, characterized in that: In step S6, the mechanical energy of the initially formed wearable armor is cooled by a cooling mechanism. After cooling, the wearable armor is removed from the mold by a demolding device, and then polished by a polishing mechanism to obtain a 3D wearable armor.
10. The composite material 3D wearable armor according to claim 9, characterized in that: In step S7, the 3D wearable armor undergoes performance testing, including tests on hardness, flexibility, abrasion resistance, and color change, to ensure that its performance meets design requirements and usage standards. After passing the tests, it is packaged using moisture-proof and anti-static packaging materials to obtain the final composite material 3D wearable armor product.